Accuracy of Clinical Examination, Lumbosacral Radiography, and Electrodiagnosis in Suspected Patients With Lumbar Herniated Nucleus Pulposus - Theresia Christin; Luther Theng; R.M. Faisal; Erial Bahar (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Low back pain is a common health problem often complained around the world with prevalence of 12% -35%2. Low back pain is the second causes of patient consult in United State of America and become the etiology of patient under 45 years old disability.3 Apart from a number of strategies recommended for the causes of low back pain, the initial diagnosis and correct diagnosis of the pain location is of clinical importance. In Indonesia, diagnostic test for lumbosacral radiography, EDX and neurological clinic examination that might help to diagnose HNP have never been compared to MRI as gold standard. Many studies have tried to find diagnostic alternatives using other modalities to help with HNP screening such as myelographic CT scans, conventional myelography or discography, but those tests are invasive. Common test that is expected to help in screening is clinical neurological examination because it is easy to do, requires no fees, can be carried out by a neurology resident supervised by a neurologist and a neurologist himself, and can be done anywhere. The accuracy of neurological clinical examinations, along with lumbosacral radiography and electrodiagnosis in assessing signs of lumbar HNP as a screening method is compared to gold standard MRI.The study is a diagnostic study with a cross sectional approach. This research was conducted at the Department of Neurology, Dr. Mohammad Hoesin Hospital Palembang in the period of 6 months from February to July 2018. The study population were patients who were suspected of having lumbar HNP. Samples were patients with suspected lumbar HNP who came to Dr. RSUP. Mohammad Hoesin Palembang and conducted a Lumbosacral MRI examination and according to the research acceptance criteria (inclusion and exclusion criteria). We find that ischialgia history, lumbosacral radiographs, upright AP projections, electroneuromyograph (ENMG) and neurological clinical examinations can be used as a screening modality in diagnosing lumbar HNP and have an accuracy that approaches the gold standard examination, namely MRI.